Participant Design Experience: A Design Proposal on the Example of IKU Akpaz Cafeteria = Katılımcı Tasarım Deneyı̇mı̇: İKÜ Akpaz Kafeterya Örneğı̇ Üzerı̇ne Bı̇r Tasarım Önerı̇sı̇ - BERZE, İPEK; YAZICI, YASEMİN ERKAN (Anadolu University, 2021)
Participation, which is a democratic understanding revises itself in the field of architecture. As opposed to established design process which takes the designer at the center, independent participatory approach takes the designer to the center and currently has a humanist understanding. It is aimed to prevent individuals from interfering with the designs after the project is implemented by taking more care of human needs. Collaborative design approach developed to minimize interventions in the physical environment is an active process guided by space users. In addition, participatory methods developed to understand the needs of users are effective in making the process democratic and sustaining projects. In this study, Istanbul Kultur University Akpaz Cafeteria was aimed to be redesigned with a participatory approach using the daily life experiences of users. Although it is university dining hall area, Akpaz Cafeteria is preferred for various purposes other than dining area by the users who have many different expectation, Akpaz Cafeteria is selected as an example for this study. The observations made to analyze the instant behavior of the users and the semi-structured interview questions directed to reveal the implicit expectations and experiences of the students constituted the participatory design methods used in the study. At the end of the study, the observations made by the designers and the interviews with the users were analyzed, and the Akpaz Cafeteria area was redesigned with the help of the findings.
Katılımcı Tasarım Deneyı̇mı̇: İKÜ Akpaz Kafeterya Örneğı̇ Üzerı̇ne Bı̇r Tasarım Önerı̇sı̇
Keywords: Co-Design; Collaborative Design; Participatory Design Experience; University Cafeteria Design